The Old-World genus Ceratothripoides (Thysanoptera: Thripidae) with a new genus for related New-World species - Mound, Laurence A.; Nickle, David A. (Zootaxa, 2009)
A key is provided to five Old World species that comprise the genus Ceratothripoides Bagnall, and the species C. revelatus (Priesner) is recalled from synonymy with C. brunneus Bagnall. Five New World species previously placed in this genus are here allocated to Retanathrips Mound & Nickle gen.n., with Physothrips funestus Hood as type species.